El aprendizaje basado en el pensamiento de Robert Swartz, como metodología activa para la enseñanza del choque cultural en la conquista de América. Tercer año BGU. - Calderón León, Mauricio Javier (2023)
Learning based on the thought of Robert Swartz, as an active methodology for teaching Culture Shock in the Conquest of America, third year BGU. Educational unit "Rumiñahui," Ambato- Ecuador. The present investigation arises since the need to implement new active methodologies in education by pedagogues towards students in the subject of History in their training process. The main objective is to make students aware of the importance of learning based on the thought of Robert Swartz, to optimize the teaching process in the BGU History Chair, Block 2: The Cultural Shock in the Conquest of America. The work is understood in the qualitative method and analysis and synthesis, on which the type of non-probabilistic sampling for convenience is based, a survey was applied, instrumented that allowed obtaining data from 22 students, in this investigation the utility was socialized of learning based on the thought of Robert Swartz in relation to the contents of the Cultural Shock in the Conquest of America, the interpretation and analysis of the results of the instrument of the study carried out was carried out, resulting in the need to use methodological strategies that meet the functionality of stimulating innovation and thought in the student body, the present research on learning based on thought helps the study and understanding of History, thus allowing the development of meaningful, reflective and critical learning in students, it is also established that its value lies in developing habits of mind, promoting creativity, criticality, academic discussion and argumentative capacity, another research discovery embarks on the fact that this methodological alternative provides teachers with a strategy that enhances their educational work by being: efficient , efficient and effective, in the way that awakens the interest of students when learning History, finally, in order to achieve a quality and warm education, it is necessary that learning based on Robert Swartz's thinking be involved in the teaching-learning process, because it responds to educational needs, finally, the recommendation is that all teachers know about this methodology and can put it into practice to optimize the teaching-learning process in students.